2019
DOI: 10.1007/s13592-019-00673-0
|View full text |Cite
|
Sign up to set email alerts
|

Nesting biology and immature stages of the oil-collecting bee Epicharis dejeanii (Apidae: Centridini)

Abstract: An aggregation of the oil-collecting bee Epicharis dejeanii Lepeletier was studied at Ilha das Flores, southern Brazil. Data on seasonality, types of floral resources collected, and nesting biology were registered. The nesting area occupied 120 m 2 with density of up to 8 nests/m 2. The tunnel entrances remained always open and surrounded by a tumulus. Adult activity lasted approximately 70 days. The females built the nest, provisioned food, and layed the egg in 4 days. The nest's architecture was very diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
14
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 22 publications
12
14
3
Order By: Relevance
“…Epicharis Klug, 1807 (Hymenoptera, Apidae, Centridini) is an exclusively Neotropical genus of bees representing about 35 species, which exhibit solitary behavior, the habit of digging their nests in the ground, usually in large aggregations (Roubik & Michener, 1980;Hiller & Wittmann, 1994;Gaglianone, 2005;Thiele & Inouye, 2007;Rocha-Filho et al, 2008;Rozen, 2016;Dec & Vivallo, 2019). Epicharis belongs to a group of approximately 400 species known as oil-collecting bees, due to the female behavior of collecting floral oils, which are used for both cell construction and larval provisions (Alves-dos-Santos et al, 2007;Gaglianone et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Epicharis Klug, 1807 (Hymenoptera, Apidae, Centridini) is an exclusively Neotropical genus of bees representing about 35 species, which exhibit solitary behavior, the habit of digging their nests in the ground, usually in large aggregations (Roubik & Michener, 1980;Hiller & Wittmann, 1994;Gaglianone, 2005;Thiele & Inouye, 2007;Rocha-Filho et al, 2008;Rozen, 2016;Dec & Vivallo, 2019). Epicharis belongs to a group of approximately 400 species known as oil-collecting bees, due to the female behavior of collecting floral oils, which are used for both cell construction and larval provisions (Alves-dos-Santos et al, 2007;Gaglianone et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Aspects of the nesting biology for different species of Epicharis, including details on the nest architecture and female behavior during nest construction and cell provisioning, have been studied in seven out of nine subgenera belonging to the genus (see Gaglianone, 2005). In general, the different species and subgenera of Epicharis studied so far construct the brood cells deep down in sandy soils (Gaglianone, 2005;Thiele & Inouye, 2007;Rocha-Filho et al, 2008;Rozen, 2016;Dec & Vivallo, 2019). Detailed nest descriptions have also been used in assessments on the evolution of nest habitat and architecture in this genus (Thiele & Inouye, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Coville et al (1983) suggested that this type of structure is plesiomorphic for Centris species, being reported in C. pallida (Alcock et al 1976;Buchmann 1990), C. cockerelli, C. rhodopus (Alcock et al 1976), C. flavifrons (Vinson and Frankie 1988;Rêgo et al 2006), C. flavofasciata (Vinson and Frankie 1999;Rozen et al 2011), and C. aethiocesta Snelling (Vinson and Frankie 1988). The construction of nests with a single brood cell, although uncommon in Centris, is frequently seen in Epicharis Klug, 1807 species, such as E. nigrita Friese (Gaglianone 2005), E. bicolor Smith (Rocha-Filho et al 2008), and E. dejeanii Lepeletier (Dec and Vivallo 2019). This type of architecture appears to be energetically inefficient when compared to a multicelled nest since females spent a lot of energy in the digging process to construct a single brood cell.…”
mentioning
confidence: 99%